Analysis of the Distribution of Train Noise Levels on the Winongo Double Track Railroad, Madiun City (Jurnal Perkeretaapian Indonesia (Indonesian Railway Journal), 2022)
Noise is an annoying sound when listened to for a long time. The standard for noise level in housing is based on KepMenLH No. 48 of 1996 worth 55 dB(A). Double track rails lead to increased rail operations and noise in the surrounding environment. This research was conducted to analyze the environmental noise level due to the train crossing the double track rail at Graha Kirana Winongo Housing, Madiun City by using a Sound Level Meter (SLM) device. Measurements were made at two points, namely at a distance of 7.5 meters and 21 meters. The results of the study the average value of environmental noise due to trains at a distance of 7.5 meters is 80 dB(A) and a distance of 21 meters is 75 dB(A). This value exceeds the standard noise level of 55 dB(A). Researchers provide mitigation in the form of suggestions for housing residents to build noise barriers or plant trees with dense leaves, and if residents are going to build new housing, it is recommended to be at a distance of 75 to 80 meters from the train tracks because the noise value at that distance is approximately 55 dB (A).